Mystical Java: The Concept of Sasahidan in Serat Wirid Hidayat Jati - Hanif Fitri Yantari; Danur Putut Permadi (Center for Research and Community Service of UIN Sultan Maulana Hasanuddin Banten-Serang City-Indonesia, 2023)
This article aims to describe the mystical Javanese Sasahidan in Serat Wirid Hidayat Jati by Raden Ngabehi Ranggawarsita with a focus on the concepts of sangkan paran and manunggaling kawula Gusti. Through literature study, with a qualitative approach, the study found that Sasahidan is the teaching of the eighth guardian council of Syekh Siti Jenar, the peak of Sheikh Siti Jenar's mystical experience is reflected in the teachings of Sasahidan. Sasahidan is a root word with shahada. About the testimony that is not only testifying, but also aware of the nature of himself, God, current life, and the universe. That way, humans can know the nature of themselves, and know their God in the sense of knowing the origin of the incident (Sangkan Paraning Dumadi). The word